Deregulation and Debureaucratization of Business Licensing Services Through The Online Single Submission (OSS) System in Local Governments Post Government Regulation Number 24 of 2018 Concerning Electronically Integrated Business Licensing Services - Mohamad Fasyehhudin; Belardo Prasetya Mega Jaya; Yogi Muhammad Rahman (Jurnal Dinamika Hukum, 2022)
Through deregulation and debureaucratization of licensing services, businesses use the Online Single Submission (OSS) system at OSS institutions, ministry, institutions, and local government, to realize increased and accelerated investment and business. This study aims to find out, analyze and answer the aspects of deregulation and debureaucratization in the context of efficiency and effectiveness of electronically integrated business licensing services using OSS in Regional Government. Important aspects of deregulation that must be considered are requirements, rights and obligations, standard operating procedures, period of validity, service time, and costs. Then, the important aspects of debureaucratization must be considered that related to institutions/departments in ministries, institutions, and local governments paying attention to the ease of service processes, human resources or service personnel who have special competencies in their fields, including effective coordination between ministries, institutions, and government at the regional level, among adequate service infrastructure, including optimizing the OSS system with advanced information technology, communication media, and convenient service areas.Keywords: deregulation, debureaucratization, public services/licensing services